2018
DOI: 10.1038/s41467-018-05198-1
|View full text |Cite
|
Sign up to set email alerts
|

Rpn11-mediated ubiquitin processing in an ancestral archaeal ubiquitination system

Abstract: While protein ubiquitination was long believed to be a truly eukaryotic feature, recently sequenced genomes revealed complete ubiquitin (Ub) modification operons in archaea. Here, we present the structural and mechanistic characterization of an archaeal Rpn11 deubiquitinase from Caldiarchaeum subterraneum, CsRpn11, and its role in the processing of CsUb precursor and ubiquitinated proteins. CsRpn11 activity is affected by the catalytic metal ion type, small molecule inhibitors, sequence characteristics at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
(92 reference statements)
0
16
0
1
Order By: Relevance
“…The catalytic groove in the MPN domain of JAMM-family DUBs accommodates the C-terminal tail of Ub for cleavage 25,26,37 . The first insertion in the JAMM core (i.e., Ins-1) forms a β-sheet with the C-terminal tail of Ub in the catalytic groove (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic groove in the MPN domain of JAMM-family DUBs accommodates the C-terminal tail of Ub for cleavage 25,26,37 . The first insertion in the JAMM core (i.e., Ins-1) forms a β-sheet with the C-terminal tail of Ub in the catalytic groove (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Archaebacteria and hadobacterium Thermus have a tagging mechanism whose tags (SAMPs) are distantly related to ubiquitin, but sampylation requires only the E1 enzyme, not E1, E2, and E3 like eukaryotic ubiquitylation (Fu et al 2016). A few filarchaeote archaebacteria (some Asgards, and thaumarchaeote Candidatus Caldiarchaeum subterraneum) have genuine ubiquitylation (Fuchs et al 2018); though that was assumed to be 'ancestral', ubiquitylation more likely evolved in eubacteria as E2 homologues abound in Planctobacteria and also occur i n Posibacteria, Cyanobacteria, and Myxococcus. Attributing all these eubacterial ubiquitylating enzymes to multiple LGTs from eukaryotes (Arcas et al 2013) seems just to reflect the widespread, essentially evidence-free, prejudice that the universal root is in the neomuran stem: in fact on their ML tree, the eukaryotic E2s are a clade robustly within paraphyletic eubacteria and closer to Planctomycetia than to most posibacterial and cyanobacterial sequences (Arcas et al 2013).…”
Section: Planctobacterial Origin Of Neomuramentioning
confidence: 99%
“…It was also once thought that ubiquitin (Ub) was restricted to eukaryotes, but Ub and ubiquitylation involving a cascade of E1, E2, and E3 enzymes is now well established in the thaumarchaeote Candidatus Caldiarchaeum subterraneum and related enzymes are known in Asgards (Fuchs et al 2018), so ubiquitylation was likely present in the last common ancestor of Filarchaeota. E2 homologues have now been discovered in Planctomycetes and in Cyanobacteria, both posibacteria phyla, and δ-proteobacterial genus Myxococcus.…”
Section: Planctobacterial Origin Of Neomuran Ubiquitin Systemmentioning
confidence: 99%
“…To verify these results in vitro, we incorporated the M. mazei MtrA-derived (5)KDPGA(10) sequence in a different protein, Caldiarchaeum subterraneum ubiquitin (26), and found that Connectase modifies it just like MtrA. Surprisingly, though, when we followed the time course of the reaction we found only a constant fraction (∼7%) of Ub-( 5)KDPGA( 10) modified at any time (Fig.…”
Section: Resultsmentioning
confidence: 83%